Measurement of flow harmonics with multi-particle cumulants in Pb+Pb collisions at [Formula: see text] TeV with the ATLAS detector - ATLAS Collaboration; Aad, G; Abbott, B; Abdallah, J; Abdel Khalek, S; Abdinov, O; Aben, R; Abi, B; Abolins, M; AbouZeid, O S; Abramowicz, H; Abreu, H; et al. (The European physical journal. C, Particles and fields, 2014)
ATLAS measurements of the azimuthal anisotropy in lead-lead collisions at [Formula: see text] TeV are shown using a dataset of approximately 7 [Formula: see text]b[Formula: see text] collected at the LHC in 2010. The measurements are performed for charged particles with transverse momenta [Formula: see text] GeV and in the pseudorapidity range [Formula: see text]. The anisotropy is characterized by the Fourier coefficients, [Formula: see text], of the charged-particle azimuthal angle distribution for [Formula: see text]-4. The Fourier coefficients are evaluated using multi-particle cumulants calculated with the generating function method. Results on the transverse momentum, pseudorapidity and centrality dependence of the [Formula: see text] coefficients are presented. The elliptic flow, [Formula: see text], is obtained from the two-, four-, six- and eight-particle cumulants while higher-order coefficients, [Formula: see text] and [Formula: see text], are determined with two- and four-particle cumulants. Flow harmonics [Formula: see text] measured with four-particle cumulants are significantly reduced compared to the measurement involving two-particle cumulants. A comparison to [Formula: see text] measurements obtained using different analysis methods and previously reported by the LHC experiments is also shown. Results of measurements of flow fluctuations evaluated with multi-particle cumulants are shown as a function of transverse momentum and the collision centrality. Models of the initial spatial geometry and its fluctuations fail to describe the flow fluctuations measurements.